2019
DOI: 10.1002/app.48653
|View full text |Cite
|
Sign up to set email alerts
|

AuNPs composites of gelatin hydrogels crosslinked by ferrocene‐containing polymer as recyclable supported catalysts

Abstract: To fabricate a recyclable supported catalyst based on gold nanoparticles (AuNPs) and gelatin hydrogel (HG) composites, a ferrocene (Fc)-containing tetrablock copolymer [P(NCHO-b-NFc-b-NTEG-b-NCHO)] was used as both reducing and stabilizing agents for AuNPs and as a crosslinker for HG. First, the effects of Fc-containing polymers, including homopolymer PNFc and copolymer P(NCHO-b-NFc-b-NTEG-b-NCHO), and different solvent systems on the morphology and aggregation of AuNPs were examined by using ultraviolet-visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Because that the dosage of NaBH 4 exceeds greatly than that of 4‐NP, the reduction reaction can be regarded as pseudo‐first‐order reaction. The apparent rate constant k is calculated from the equation: ln()CtC0=knormalt where C t /C 0 represents the ratio of 4‐NP concentrations at time t and 0, which is calculated from their corresponding absorption intensity in UV–Vis spectra 33 . The linear fit of ln ( C t / C 0 ) versus time t with Fe 3 O 4 /PANI/Au(Sol) ( k = 0.04771 s −1 ) and Fe 3 O 4 /PANI/Au(In Situ) ( k = 0.02296 s −1 ) as catalysts is shown in Figure 5c.…”
Section: Resultsmentioning
confidence: 99%
“…Because that the dosage of NaBH 4 exceeds greatly than that of 4‐NP, the reduction reaction can be regarded as pseudo‐first‐order reaction. The apparent rate constant k is calculated from the equation: ln()CtC0=knormalt where C t /C 0 represents the ratio of 4‐NP concentrations at time t and 0, which is calculated from their corresponding absorption intensity in UV–Vis spectra 33 . The linear fit of ln ( C t / C 0 ) versus time t with Fe 3 O 4 /PANI/Au(Sol) ( k = 0.04771 s −1 ) and Fe 3 O 4 /PANI/Au(In Situ) ( k = 0.02296 s −1 ) as catalysts is shown in Figure 5c.…”
Section: Resultsmentioning
confidence: 99%
“…The first weight-loss mainly occurs at 50-120°C, too, and the corresponding mass-loss ratios are 21.8% for the MWH sample and 19.1% for the WBH control, respectively. This mainly results from the removal of H 2 O and other volatile small-size substances in tanned skin pieces [45]. The obvious weight-loss process on the TG curves is the second stage from 200 to 500°C, which mainly resulted from the break of cross-linking bonds between collagen fibers [41].…”
Section: Thermal Analysismentioning
confidence: 99%
“…In particular, all kinds of ferrocene (Fc)-containing polymers with precise structures and MWs can also be controllably prepared through the direct ROMP of Fc-containing norbornene-based monomers under the initiation of the third-generation Grubbs' catalyst [21]. It was confirmed that the presence of the sandwich-like Fc complex has no effect on the catalytic activity of Grubbs' catalyst, leading to molecular level control of the resulting polymers and materials for various functional applications [22,23]. However, the direct ROMP of supramolecular monomers, for example, those containing host-guest complexes of β-cyclodextrin (β-CD)/Fc, is still a major challenge [24].…”
Section: Introductionmentioning
confidence: 99%